Host urine immunological biomarkers as potential candidates for the diagnosis of tuberculosis. (October 2020) - Eribo, Osagie A.; Leqheka, Monkoe S.; Malherbe, Stephanus T.; McAnda, Shirley; Stanley, Kim; van der Spuy, Gian D.; Walzl, Gerhard; Chegou, Novel N.
Highlights: Twenty-nine host biomarkers were evaluated in urine samples obtained from TB suspects. Seven individual biomarkers showed potential as promising diagnostic candidates. A four-marker urinary biosignature diagnosed TB with high accuracy  in HIV-positive participants. Urinary inflammatory protein biomarkers are promising as TB diagnostic candidates. Abstract: Objective: To investigate the potential of host urinary biomarkers as diagnostic candidates for tuberculosis (TB). Methods: Adults self-presenting with symptoms requiring further investigation for TB were enrolled in Cape Town, South Africa. Participants were later classified as having TB or other respiratory diseases (ORD) using results from TB confirmatory tests. The concentrations of 29 analytes were evaluated in urine samples from participants using the Luminex platform, and their diagnostic potential was assessed using standard statistical approaches. Results: Of the 151 study participants, 34 (22.5%) were diagnosed with TB and 26 (17.2%) were HIV-positive. Seven biomarkers showed potential as TB diagnostic candidates, with accuracy improving (in HIV-positives) when stratified according to HIV status (area under the receiver operating characteristics curve; AUC ≥0.80). In HIV-positive participants, a four-marker biosignature (sIL6R, MMP-9, IL-2Ra, IFN-γ) diagnosed TB with AUC of 0.96, sensitivity of 85.7% (95% confidence interval (CI) 42.1–99.6%), and specificity of 94.7% (95% CI 74.0–99.9%). In HIV-negatives, the most promising was a two-marker biosignature (sIL6R and sIL-2Ra), which diagnosed TB with AUC of 0.76, sensitivity of 53.9% (95% CI 33.4–73.4%), and specificity of 79.6% (95% CI 70.3–87.1%). Conclusions: Urinary host inflammatory biomarkers possess TB diagnostic potential but may be influenced by HIV infection. The results of this study require validation in larger studies.